Paradoxical Effects of Performance Pressure on Employees’ In-Role Behaviors: An Approach/Avoidance Model - Xu, Xiaofeng; Wang, Yihui; Li, Miaomiao; Kwan, Ho Kwong (Frontiers in Psychology, 2021)
Performance pressure acts as a double-edged sword for employees. Based on an approach/avoidance framework, we theorize that performance pressure produces both positive and negative effects on employees’ in-role behaviors via approach motivation (i.e., self-objectification) and avoidance motivation (i.e., workplace anxiety), and work meaningfulness moderate employees’ reactions to performance pressure. We examine our hypotheses using data from a sample of 345 employees in various organizations. The results show that self-objectification provides an approach motive that mediates the positive indirect effect of performance pressure on employees’ in-role behaviors. However, workplace anxiety provides an avoidance motive that mediates the negative indirect effect of performance pressure on employees’ in-role behaviors. Work meaningfulness strengthens both the approach and avoidance tendencies that employees experience under performance pressure. Our findings have significant theoretical and managerial implications.